2009
DOI: 10.1111/j.1600-0625.2009.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of a cream containing Dead Sea minerals against UVB‐induced stress in human skin

Abstract: Our results clearly show that Dermud has protective, anti-oxidant and anti-inflammatory properties that can antagonize biological effects of UVB irradiation in skin. It may therefore be able to reduce skin photodamage and photoaging, and more generally to reduce oxidative stress and inflammation in skin pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 71 publications
0
56
1
1
Order By: Relevance
“…Several studies have shown that skin cell lines cultivated in vitro and treated with different pollutants are characterized by increased production of pro-inflammatory compounds [38][39][40]. HaCaT (cultured human keratinocyte) cells in the presence of particulate matter released increased amounts of transforming growth factor (TNF-α) and interleukins (IL-1α and IL-8), which resulted in the accumulation of the inflammatory cells causing an inflammatory response [39].…”
Section: Induction Of Inflammatory Cascadementioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that skin cell lines cultivated in vitro and treated with different pollutants are characterized by increased production of pro-inflammatory compounds [38][39][40]. HaCaT (cultured human keratinocyte) cells in the presence of particulate matter released increased amounts of transforming growth factor (TNF-α) and interleukins (IL-1α and IL-8), which resulted in the accumulation of the inflammatory cells causing an inflammatory response [39].…”
Section: Induction Of Inflammatory Cascadementioning
confidence: 99%
“…The microscopic images allow one to observe morphological changes in the epidermal and dermal cells or the density and structure of the collagen network, after exposure to pollution [39,51]. Cell viability in response to stress factors can be also estimated by caspase 3 activity, which is a marker for cell apoptosis [38].…”
Section: In Vitro Efficacy Testingmentioning
confidence: 99%
See 3 more Smart Citations